Dynamics of movement amplitude indicators in joints of patients with rheumatoid arthritis - Grygus , I.M.; Nogas , A.O.; Zdanyuk , V.V. (Medicni Perspektivi, 2023)
The purpose of the paper is to evaluate the effectiveness of the technology of rehabilitation measures in patients with rheumatoid arthritis according to the dynamics of movements amplitude indicators. Theoretical (analysis and generalization of literary and Internet data), survey, collection of anamnesis, objective examination, anthropometric (goniometry) methods of mathematical statistics. 188 patients with rheumatoid arthritis were examined, of which 156 (83%) were women, 32 (17%) were men, average age was 44.9±7.6 years. The analysis of the goniometric indicators of the joints of hands affected by rheumatoid arthritis after six months of conducted rehabilitation measures showed a significant improvement in the mobility of the radiocarpal joint and hand fingers in the examined patients. In particular, active flexion in the radiocarpal joint significantly increased in patients of the experimental group and was 72.5±6.0º, while in the patients of the control group this indicator was 5.3º less (67.2±5.0º) (р<0.05). A significant result was achieved in restoring flexion of the hand fingers in patients of the experimental group: mobility of the fingers in the metacarpal phalangeal joints was 83.2±3.6º, and in the control group it was 73.4±5.0º, in the proximal interphalangeal joints in patients of the experimental group it was 84.1±3.3º, and in the control group – 67.8±4.8º (р<0.05). Positive dynamics of active movements in the foot and finger joints was also observed in patients of both groups at the end of the study. In the patients of the experimental group, the active dorsiflexion in the ankle joint was 27.7±1.4º, the plantar flexion was 41.3±1.8º, which was significantly better than in patients of the control group in which the observed dorsiflexion was 23.4±1.7º, and plantar flexion – 41.3±1.8º (р<0.05). Accordingly, there was a significant increase in the motor function indicators in the metatarsal phalangeal joints of patients in the experimental group: flexion was up to 37.1±1.4º, extension – up to 39.2±1.0º, compared with the indicators in the control group: flexion – up to 33.5±1.2º, extension – up to 36.2±1.1º (р<0.05). The effectiveness of the developed technology is confirmed by improvement of the results of goniometric indicators in patients of the experimental group compared with the control group.